Whole-Body MRI in Oncology: Focus on 3D Sequences in Musculoskeletal Oncology - Laura Fayad; Ali Ghasemi; Shivani Ahlawat (EMJ Radiology)
Whole-body magnetic resonance imaging (WB-MRI) has significantly improved oncological disease management by enabling comprehensive visualisation of the entire body in a single scan, facilitating the diagnosis, staging, and monitoring of various cancers. Its integration with diffusion-weighted imaging and apparent diffusion coefficient mapping offers quantitative insights into tumour biology, notably enhancing treatment planning and response evaluation. The evolution from 2D to 3D WB-MRI has improved image resolution and reduced scan times. This review underscores the pivotal role of WB-MRI in oncology, highlighting its efficiency in detecting and characterising tumours and assessing treatment response with a focus on 3D techniques.